ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI ANGGOTA UPKD PASCA PROYEK BRDP (Studi Kasus UPKD Sidodadi di Desa Sidodadi Kec. Pondok Kelapa Kab. Bengkulu Utara) - Sumantri, Bambang; Cahyadinata, Indra; Surbakti, Anastasia (Jurnal AGRISEP, 2007)
This research aimed to knowthe class of participated member sidodadi UPKD pasca BRDP and to know the factors related to participated from the customers of Sidodadi UPKD pasca BRDP in North Bengkulu, by using primary and secondary data. Data was taken from 71 samples of costumers by using Simple Random Sampling. The analysis data which been used in this research was Spearman Rank by using two tail of t-test by confidence level of 95 % (a=0,025). The research result shows that variable of education, the long time as member and household income show significanly with class partitipation, while the other of variabels are family members and perception were not significantly to class participation